IML ink capable of resisting injection molding high-temperature impact
By adding a specific proportion of pigments, resins, solvents and plasticizers to the IML ink, the problem of excessive cross-linking of ink during high-temperature injection molding is solved, and the high-temperature performance of the ink layer is improved and peeling force is improved, which is suitable for injection molding of in-mold inserts.
Patent Information
- Application Number
- CN202411718391.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-11
AI Technical Summary
Existing IML inks are prone to excessive crosslinking during high-temperature injection molding, resulting in brittleness, loss of flexibility, and easy peeling.
An IML ink including a specific weight percentage component is provided, specifically: 10 wt% to 30 wt% pigment, 25 wt% to 45 wt% resin, 30 wt% to 50 wt% solvent and 5 wt% to 15 wt% plasticizer. Among them, the plasticizer may be a composite plasticizer one to four, the resin is a thermoplastic polyurethane resin, and the solvent is ethanol, isopropanol or n-propanol.
The ink has excellent performance in high temperature performance, with peeling force, color aberration, color penetration and adhesion fastness all reaching expectations, and has high comprehensive performance, which is suitable for injection molding of in-mold inserts.
Smart Images

Figure BDA0005157423410000041 
Figure BDA0005157423410000051 
Figure BDA0005157423410000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inks, and in particular to an IML ink capable of resisting injection molding high temperature impact. Background Art
[0002] IML is also called in-mold injection molding. Its workpiece has the following very notable features: the surface is a hardened transparent film, the middle is a printed pattern layer, and the back is a plastic layer. Because the ink is sandwiched in the middle, the product surface is not easily scratched, the friction resistance is also better, and the color can be kept bright for a long time and is not easy to fade.
[0003] After the ink is printed and solidified, it will go through a high-temperature injection molding process again, which is likely to cause some components in the ink to undergo excessive cross-linking reactions. Under the action of high temperature and injection molding pressure, the resin in the ink may further polymerize to form an over-cross-linked structure. This structure will make the ink layer brittle and hard, and lose its flexibility. After the ink layer becomes brittle, when the product is subjected to external forces, such as collision, bending, etc., the ink layer is prone to peeling.
[0004] Therefore, it is necessary to design an IML ink that can resist the high temperature impact of injection molding. Summary of the invention
[0005] The present invention aims at the deficiencies in the prior art and provides the following technical solutions:
[0006] An IML ink capable of resisting high temperature impact of injection molding comprises the following components in percentage by weight:
[0007] 10wt%-30wt% of pigment, 25wt%-45wt% of resin, 30wt%-50wt% of solvent and 5wt%-15wt% of plasticizer.
[0008] As an improvement of the above technical solution, the ink comprises the following components in weight percentage:
[0009] 10wt% pigment, 40wt% resin, 45wt% solvent and 5wt% plasticizer.
[0010] As an improvement of the above technical solution, the ink comprises the following components in weight percentage:
[0011] 20wt% pigment, 35wt% resin, 35wt% solvent and 10wt% plasticizer.
[0012] As an improvement of the above technical solution, the ink comprises the following components in weight percentage:
[0013] 30wt% pigment, 25wt% resin, 30wt% solvent and 15wt% plasticizer.
[0014] As an improvement of the above technical solution, the plasticizer is any one of composite plasticizer 1, composite plasticizer 2, composite plasticizer 3, and composite plasticizer 4.
[0015] As an improvement of the above technical solution, the composite plasticizer 1 comprises at least the following components in parts by weight:
[0016] 80-85 parts of chloropalm oil methyl ester, 10-25 parts of epoxidized vegetable oil, 0.5-1 parts of epoxy resin active diluent, 1.5-3 parts of antioxidant, 1.5-2 parts of coupling agent.
[0017] As an improvement of the above technical solution, the composite plasticizer 2 comprises at least the following components in parts by weight:
[0018] 10-12 parts of trimellitic anhydride, 22-30 parts of C8-10 fatty alcohol, 0.5-3 parts of isopropyl titanate, 0.5-2.5 parts of sodium carbonate, and 0.8-2 parts of activated carbon.
[0019] As an improvement of the above technical solution, the composite plasticizer three comprises at least the following components in parts by weight:
[0020] 2.5-3 parts of nano silicon dioxide, 22-30 parts of ethoxylated alkylamine, 42-45 parts of methyl hydrogen silicone oil, 6.5-7 parts of hydroxy polydimethylsiloxane, 5.5-6 parts of vinyl trimethoxy silane, 4.5-4.8 parts of ammonium polyphosphate, 1.5-1.8 parts of alkyl glycidyl ether, 2.5-2.8 parts of maleic anhydride grafted modified polypropylene, 1-1.2 parts of vinyl tributyl ketoxime silane, and 0.3-0.5 parts of mixed rare earth chloride.
[0021] As an improvement of the above technical solution, the composite plasticizer 4 comprises at least the following components in parts by weight:
[0022] 13-16 parts of nano-montmorillonite, 5.5-6 parts of fumed silica, 2.5-3 parts of nano-zinc oxide, 22-25 parts of γ-aminopropyltriethoxysilane, 5-5.5 parts of alkylphenol polyoxyethylene ether, and 0.5-1 part of mixed rare earth chloride.
[0023] As an improvement of the above technical solution, the resin is a thermoplastic polyurethane resin, and the solvent is any one of ethanol, isopropanol or n-propanol.
[0024] Beneficial effects of the present invention:
[0025] The ink prepared according to the formula provided by the present invention has excellent high temperature performance, and the peeling force, color difference, color penetration and adhesion strength can meet expectations. It also has high comprehensive performance in in-mold insert injection molding and has broad application prospects. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0027] The resin in the existing ink may further polymerize under the action of high temperature and injection pressure to form an over-crosslinked structure. This structure will make the ink layer brittle and hard, and lose its flexibility. After the ink layer becomes brittle, it is easy to peel off when the product is subjected to external forces, such as collision, bending, etc.
[0028] To solve the above problems, the present invention provides a technical solution to the above technical problems.
[0029] Embodiment 1
[0030] It should be noted that, in this embodiment, the ink includes the following components in percentage by weight:
[0031] 10wt%-30wt% of pigment, 25wt%-45wt% of resin, 30wt%-50wt% of solvent and 5wt%-15wt% of plasticizer, wherein the resin is thermoplastic polyurethane resin and the solvent is ethanol.
[0032] Wherein, the plasticizer comprises the following components in parts by weight:
[0033] 80 parts of chloropalm oil methyl ester, 10 parts of epoxidized vegetable oil, 0.5 parts of epoxy resin active diluent, 1.5 parts of antioxidant, 1.5 parts of coupling agent. Among them, the epoxy resin active diluent is butanediol glycidyl ether, the antioxidant is antioxidant 1076, and the coupling agent is isopropyl triisostearoyl titanate.
[0034] The ink is prepared by a conventional method for preparing ink.
[0035] Testing principle: After the ink is printed, prepare the packaging bag sample, and test the sample bag color, the peeling force between the composite layers, the adhesion of the ink to the substrate, whether the sample bag has color penetration and other indicators under the specified time, pressure and temperature to evaluate the ink's resistance to retorting (high temperature resistance). Refer to the industry standard QB / T5344-201X, high temperature retorting grade (121℃-145℃).
[0036] Peeling force: Test the peeling force between two substrates with ink as the middle layer (including the values before and after steaming). Execute in accordance with GB8808-1988.
[0037] Color difference: Test the color change of the printed ink image on the sample bag before and after cooking.
[0038] Color penetration: Observe the sample bag and water after cooking to see if there is any penetration.
[0039] Adhesion fastness: Test the adhesion fastness of ink on the printed substrate (including the values before and after cooking) in accordance with GB / T13217.7-2009 liquid ink adhesion fastness test method.
[0040] The specific test parameters are shown in Table 1:
[0041] Before and after steaming Peel force Chromatic Aberration Color penetration Adhesion fastness / % Before cooking 24.15N No change No change 99.96 After cooking 23.33N No change No change 98.34
[0042] As shown in Table 1 above, the ink prepared by the above formula has excellent high temperature performance, and the peeling force, color difference, color penetration and adhesion fastness can meet expectations.
[0043] Embodiment 2-3
[0044] Compared with Example 1, the following weight parts of the plasticizer are different, as shown in Table 2:
[0045]
[0046] The ink is prepared by a conventional method for preparing ink.
[0047] Testing principle: After the ink is printed, prepare the packaging bag sample, and test the sample bag color, the peeling force between the composite layers, the adhesion of the ink to the substrate, whether the sample bag has color penetration and other indicators under the specified time, pressure and temperature to evaluate the ink's resistance to retorting (high temperature resistance). Refer to the industry standard QB / T5344-201X, high temperature retorting grade (121℃-145℃).
[0048] Peeling force: Test the peeling force between two substrates with ink as the middle layer (including the values before and after steaming). Execute in accordance with GB8808-1988.
[0049] Color difference: Test the color change of the printed ink image on the sample bag before and after cooking.
[0050] Color penetration: Observe the sample bag and water after cooking to see if there is any penetration.
[0051] Adhesion fastness: Test the adhesion fastness of ink on the printed substrate (including the values before and after cooking) in accordance with GB / T13217.7-2009 liquid ink adhesion fastness test method.
[0052] The specific test parameters are shown in Table 3:
[0053]
[0054] As shown in Table 3 above, the ink prepared by the above formula has excellent high temperature performance, and the peeling force, color difference, color penetration, and adhesion fastness can all meet expectations. And compared with Example 1 and Example 3, the ink prepared by the ratio given in Example 2 is the most excellent.
[0055] Embodiment 4
[0056] Compared with Example 1, the components of the plasticizer are different.
[0057] In this embodiment, the plasticizer includes the following components in parts by weight:
[0058] 10 parts of trimellitic anhydride, 22 parts of C8-10 fatty alcohol, 0.5 parts of isopropyl titanate, 0.5 parts of sodium carbonate, and 0.8 parts of activated carbon.
[0059] The ink is prepared by a conventional method for preparing ink.
[0060] Testing principle: After the ink is printed, prepare the packaging bag sample, and test the sample bag color, the peeling force between the composite layers, the adhesion of the ink to the substrate, whether the sample bag has color penetration and other indicators under the specified time, pressure and temperature to evaluate the ink's resistance to retorting (high temperature resistance). Refer to the industry standard QB / T5344-201X, high temperature retorting grade (121℃-145℃).
[0061] Peeling force: Test the peeling force between two substrates with ink as the middle layer (including the values before and after steaming). Execute in accordance with GB8808-1988.
[0062] Color difference: Test the color change of the printed ink image on the sample bag before and after cooking.
[0063] Color penetration: Observe the sample bag and water after cooking to see if there is any penetration.
[0064] Adhesion fastness: Test the adhesion fastness of ink on the printed substrate (including the values before and after cooking) in accordance with GB / T13217.7-2009 liquid ink adhesion fastness test method.
[0065] The specific test parameters are shown in Table 4:
[0066] Before and after steaming Peel force Chromatic Aberration Color penetration Adhesion fastness / % Before cooking 24.25N No change No change 99.86 After cooking 23.13N No change No change 98.12
[0067] As shown in Table 4 above, the ink prepared using the above formula has excellent high temperature performance, and the peeling force, color difference, color penetration, and adhesion fastness can all meet expectations.
[0068] Embodiment 5-6
[0069] Compared with Example 4, the plasticizer includes the following components in parts by weight, as shown in Table 5:
[0070] Example Trimellitic anhydride C8-10 fatty alcohol Isopropyl Titanate Sodium carbonate Activated carbon Embodiment 5 11 26 1.75 1.5 1.4 Embodiment 6 12 30 3 2.5 2
[0071] The ink is prepared by a conventional method for preparing ink.
[0072] Testing principle: After the ink is printed, prepare the packaging bag sample, and test the sample bag color, the peeling force between the composite layers, the adhesion of the ink to the substrate, whether the sample bag has color penetration and other indicators under the specified time, pressure and temperature to evaluate the ink's resistance to retorting (high temperature resistance). Refer to the industry standard QB / T5344-201X, high temperature retorting grade (121℃-145℃).
[0073] Peeling force: Test the peeling force between two substrates with ink as the middle layer (including the values before and after steaming). Execute in accordance with GB8808-1988.
[0074] Color difference: Test the color change of the printed ink image on the sample bag before and after cooking.
[0075] Color penetration: Observe the sample bag and water after cooking to see if there is any penetration.
[0076] Adhesion fastness: Test the adhesion fastness of ink on the printed substrate (including the values before and after cooking) in accordance with GB / T13217.7-2009 liquid ink adhesion fastness test method.
[0077] The specific test parameters are shown in Table 6:
[0078]
[0079] As shown in Table 6 above, the ink prepared by the above formula has excellent high temperature performance, and the peeling force, color difference, color penetration, and adhesion fastness can all meet expectations. And compared with Example 4 and Example 6, the ink prepared by the ratio given in Example 5 is the most excellent.
[0080] Embodiment 7
[0081] Compared with Example 1, the components of the plasticizer are different.
[0082] In this embodiment, the plasticizer includes the following components in parts by weight:
[0083] 2.5 parts of nano-silica, 22 parts of ethoxylated alkylamine, 42 parts of methyl hydrogen silicone oil, 6.5 parts of hydroxy polydimethylsiloxane, 5.5 parts of vinyl trimethoxy silane, 4.5 parts of ammonium polyphosphate, 1.5 parts of alkyl glycidyl ether, 2.5 parts of maleic anhydride grafted modified polypropylene, 1 part of vinyl trisbutyl ketoxime silane, and 0.3 parts of mixed rare earth chloride.
[0084] The ink is prepared by a conventional method for preparing ink.
[0085] Testing principle: After the ink is printed, prepare the packaging bag sample, and test the sample bag color, the peeling force between the composite layers, the adhesion of the ink to the substrate, whether the sample bag has color penetration and other indicators under the specified time, pressure and temperature to evaluate the ink's resistance to retorting (high temperature resistance). Refer to the industry standard QB / T5344-201X, high temperature retorting grade (121℃-145℃).
[0086] Peeling force: Test the peeling force between two substrates with ink as the middle layer (including the values before and after steaming). Execute in accordance with GB8808-1988.
[0087] Color difference: Test the color change of the printed ink image on the sample bag before and after cooking.
[0088] Color penetration: Observe the sample bag and water after cooking to see if there is any penetration.
[0089] Adhesion fastness: Test the adhesion fastness of ink on the printed substrate (including the values before and after cooking) in accordance with GB / T13217.7-2009 liquid ink adhesion fastness test method.
[0090] The specific test parameters are shown in Table 7:
[0091] Before and after steaming Peel force Chromatic Aberration Color penetration Adhesion fastness / % Before cooking 25.67N No change No change 99.45 After cooking 23.93N No change No change 97.89
[0092] As shown in Table 7 above, the ink prepared using the above formula has excellent high temperature performance, and the peeling force, color difference, color penetration, and adhesion fastness can all meet expectations.
[0093] Embodiment 8-9
[0094] Compared with Example 7, the plasticizer includes the following components in parts by weight, as shown in Table 8:
[0095] Components Embodiment 8 Embodiment 9 Nano Silica 2.75 3 Ethoxylated alkyl amines 26 30 Methyl hydrogen silicone oil 43.5 45 Hydroxydimethicone 6.75 7 Vinyltrimethoxysilane 5.75 6 Ammonium Polyphosphate 4.65 4.8 Alkyl glycidyl ether 1.65 1.8 Maleic anhydride grafted modified polypropylene 2.65 2.8 Vinyl trisbutyl ketoxime silane 1.1 1.2 Mixed rare earth chloride 0.4 0.5
[0096] The ink is prepared by a conventional method for preparing ink.
[0097] Testing principle: After the ink is printed, prepare the packaging bag sample, and test the sample bag color, the peeling force between the composite layers, the adhesion of the ink to the substrate, whether the sample bag has color penetration and other indicators under the specified time, pressure and temperature to evaluate the ink's resistance to retorting (high temperature resistance). Refer to the industry standard QB / T5344-201X, high temperature retorting grade (121℃-145℃).
[0098] Peeling force: Test the peeling force between two substrates with ink as the middle layer (including the values before and after steaming). Execute in accordance with GB8808-1988.
[0099] Color difference: Test the color change of the printed ink image on the sample bag before and after cooking.
[0100] Color penetration: Observe the sample bag and water after cooking to see if there is any penetration.
[0101] Adhesion fastness: Test the adhesion fastness of ink on the printed substrate (including the values before and after cooking) in accordance with GB / T13217.7-2009 liquid ink adhesion fastness test method.
[0102] The specific test parameters are shown in Table 9:
[0103]
[0104]
[0105] As shown in Table 9 above, the ink prepared by the above formula has excellent high temperature performance, and the peeling force, color difference, color penetration, and adhesion fastness can all meet expectations. And compared with Example 7 and Example 9, the ink prepared by the ratio given in Example 8 is the most excellent.
[0106] Embodiment 10
[0107] Compared with Example 1, the components of the plasticizer are different.
[0108] In this embodiment, the plasticizer includes the following components in parts by weight:
[0109] 13 parts of nano-montmorillonite, 5.5 parts of fumed silica, 2.5 parts of nano-zinc oxide, 22 parts of γ-aminopropyltriethoxysilane, 5 parts of alkylphenol polyoxyethylene ether, and 0.5 parts of mixed rare earth chloride.
[0110] The ink is prepared by a conventional method for preparing ink.
[0111] Testing principle: After the ink is printed, prepare the packaging bag sample, and test the sample bag color, the peeling force between the composite layers, the adhesion of the ink to the substrate, whether the sample bag has color penetration and other indicators under the specified time, pressure and temperature to evaluate the ink's resistance to retorting (high temperature resistance). Refer to the industry standard QB / T5344-201X, high temperature retorting grade (121℃-145℃).
[0112] Peeling force: Test the peeling force between two substrates with ink as the middle layer (including the values before and after steaming). Execute in accordance with GB8808-1988.
[0113] Color difference: Test the color change of the printed ink image on the sample bag before and after cooking.
[0114] Color penetration: Observe the sample bag and water after cooking to see if there is any penetration.
[0115] Adhesion fastness: Test the adhesion fastness of ink on the printed substrate (including the values before and after cooking) in accordance with GB / T13217.7-2009 liquid ink adhesion fastness test method.
[0116] The specific test parameters are shown in Table 10:
[0117]
[0118]
[0119] As shown in Table 10 above, the ink prepared using the above formula has excellent high temperature performance, and the peeling force, color difference, color penetration, and adhesion fastness can all meet expectations.
[0120] Embodiment 11-12
[0121] Compared with Example 10, the following weight parts of the plasticizer are different, as shown in Table 11:
[0122] Components Embodiment 11 Embodiment 12 Nano-montmorillonite 14.5 16 Fumed silica 5.75 6 Nano zinc oxide 2.75 3 γ-Aminopropyltriethoxysilane 23.5 25 Alkylphenol polyoxyethylene ether 5.25 5.5 Mixed rare earth chloride 0.75 1
[0123] The ink is prepared by a conventional method for preparing ink.
[0124] Testing principle: After the ink is printed, prepare the packaging bag sample, and test the sample bag color, the peeling force between the composite layers, the adhesion of the ink to the substrate, whether the sample bag has color penetration and other indicators under the specified time, pressure and temperature to evaluate the ink's resistance to retorting (high temperature resistance). Refer to the industry standard QB / T5344-201X, high temperature retorting grade (121℃-145℃).
[0125] Peeling force: Test the peeling force between two substrates with ink as the middle layer (including the values before and after steaming). Execute in accordance with GB8808-1988.
[0126] Color difference: Test the color change of the printed ink image on the sample bag before and after cooking.
[0127] Color penetration: Observe the sample bag and water after cooking to see if there is any penetration.
[0128] Adhesion fastness: Test the adhesion fastness of ink on the printed substrate (including the values before and after cooking) in accordance with GB / T13217.7-2009 liquid ink adhesion fastness test method.
[0129] The specific test parameters are shown in Table 12:
[0130]
[0131] As shown in Table 12 above, the ink prepared by the above formula has excellent high temperature performance, and the peeling force, color difference, color penetration, and adhesion fastness can all meet expectations. And compared with Example 10 and Example 12, the ink prepared by the ratio given in Example 11 is the most excellent.
[0132] Comparative Example 1
[0133] It should be noted that the ink includes the following components in conventional proportions: pigment, resin, and solvent.
[0134] The ink is prepared by a conventional method for preparing ink.
[0135] Testing principle: After the ink is printed, prepare the packaging bag sample, and test the sample bag color, the peeling force between the composite layers, the adhesion of the ink to the substrate, whether the sample bag has color penetration and other indicators under the specified time, pressure and temperature to evaluate the ink's resistance to retorting (high temperature resistance). Refer to the industry standard QB / T5344-201X, high temperature retorting grade (121℃-145℃).
[0136] Peeling force: Test the peeling force between two substrates with ink as the middle layer (including the values before and after steaming). Execute in accordance with GB8808-1988.
[0137] Color difference: Test the color change of the printed ink image on the sample bag before and after cooking.
[0138] Color penetration: Observe the sample bag and water after cooking to see if there is any penetration.
[0139] Adhesion fastness: Test the adhesion fastness of ink on the printed substrate (including the values before and after cooking) in accordance with GB / T13217.7-2009 liquid ink adhesion fastness test method.
[0140] The specific test parameters are shown in Table 13:
[0141] Before and after steaming Peel force Chromatic Aberration Color penetration Adhesion fastness / % Before cooking 22.15N No change No change 98.76 After cooking 20.33N change change 97.04
[0142] As shown in Table 13 above, the ink made with the conventional formula has poorer high temperature performance in terms of peeling force, color difference, color penetration, and adhesion compared to the ink with the addition of plasticizer. The color difference and color penetration show obvious changes after high temperature.
[0143] Comparing the data obtained in Examples 1 to 12, it can be seen that the ink prepared by the ratio of Example 2 has the best performance in terms of adhesion fastness, and the ink prepared by the ratio of Example 5 has the best peeling performance.
[0144] It can be seen that the ink formula provided by the present invention has high comprehensive performance in in-mold insert injection molding and has broad application prospects.
[0145] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them.
[0146] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
[0147] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. The present invention is therefore not limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. An IML ink that can resist high temperature impact of injection molding, characterized in that: The following components are included in weight percentage: 10wt%-30wt% of pigment, 25wt%-45wt% of resin, 30wt%-50wt% of solvent and 5wt%-15wt% of plasticizer.
2. The IML ink capable of resisting high temperature impact of injection molding according to claim 1, characterized in that: The following components are included in weight percentage: 10wt% pigment, 40wt% resin, 45wt% solvent and 5wt% plasticizer.
3. The IML ink capable of resisting high temperature impact of injection molding according to claim 1, characterized in that: The following components are included in weight percentage: 20wt% pigment, 35wt% resin, 35wt% solvent and 10wt% plasticizer.
4. The IML ink capable of resisting high temperature impact of injection molding according to claim 1, characterized in that: The following components are included in weight percentage: 30wt% pigment, 25wt% resin, 30wt% solvent and 15wt% plasticizer.
5. An IML ink capable of resisting high temperature impact of injection molding according to any one of claims 1 to 4, characterized in that: The plasticizer is any one of composite plasticizer 1, composite plasticizer 2, composite plasticizer 3 and composite plasticizer 4.
6. The IML ink capable of resisting high temperature impact of injection molding according to claim 5, characterized in that: The composite plasticizer 1 at least comprises the following components in parts by weight: 80-85 parts of chloropalm oil methyl ester, 10-25 parts of epoxidized vegetable oil, 0.5-1 parts of epoxy resin active diluent, 1.5-3 parts of antioxidant, 1.5-2 parts of coupling agent.
7. The IML ink capable of resisting high temperature impact of injection molding according to claim 5, characterized in that: The composite plasticizer 2 at least comprises the following components in parts by weight: 10-12 parts of trimellitic anhydride, 22-30 parts of C8-10 fatty alcohol, 0.5-3 parts of isopropyl titanate, 0.5-2.5 parts of sodium carbonate, and 0.8-2 parts of activated carbon.
8. The IML ink capable of resisting high temperature impact of injection molding according to claim 5, characterized in that: The composite plasticizer three comprises at least the following components in parts by weight: 2.5-3 parts of nano silicon dioxide, 22-30 parts of ethoxylated alkylamine, 42-45 parts of methyl hydrogen silicone oil, 6.5-7 parts of hydroxy polydimethylsiloxane, 5.5-6 parts of vinyl trimethoxy silane, 4.5-4.8 parts of ammonium polyphosphate, 1.5-1.8 parts of alkyl glycidyl ether, 2.5-2.8 parts of maleic anhydride grafted modified polypropylene, 1-1.2 parts of vinyl tributyl ketoxime silane, and 0.3-0.5 parts of mixed rare earth chloride.
9. The IML ink capable of resisting high temperature impact of injection molding according to claim 5, characterized in that: The composite plasticizer 4 comprises at least the following components in parts by weight: 13-16 parts of nano-montmorillonite, 5.5-6 parts of fumed silica, 2.5-3 parts of nano-zinc oxide, 22-25 parts of γ-aminopropyltriethoxysilane, 5-5.5 parts of alkylphenol polyoxyethylene ether, and 0.5-1 part of mixed rare earth chloride.
10. An IML ink capable of resisting high temperature impact of injection molding according to any one of claims 1 to 4, characterized in that: The resin is a thermoplastic polyurethane resin, and the solvent is any one of ethanol, isopropanol or n-propanol.